Evaluation of the floral vasculature of the Janusia, Mascagnia and Tetrapterys species as a tool to explain the decrease of floral organs in Malpighiaceae - Souto, Letícia Silva [UNESP]; Oliveira, Denise Maria Trombert (Elsevier, 2013)
The family Malpighiaceae is considered monophyletic, but the intra-family classification is conflicting. Analyses of floral vasculature allow the identification of reductions, connations and adnations and can even reveal evolutionary steps prior to current floral morphology. The present work analysed the floral vasculature of Janusia mediterranea, Mascagnia cordifolia and Tetrapterys chamaecerasifolia using material processed by traditional methods for light microscopy. A general pattern was observed of three bundle traces supplying each sepal and one trace per petal and stamen; Mascagnia is an exception, as its eglandular sepal has only a median trace but shares lateral traces with adjacent sepals. No dorsal traces are emitted to the carpels; however, three intercarpellary complexes are emitted that divide into six ventral bundles, supplying the ovule. Mascagnia demonstrates connation between the anterior and adjacent sepal glands; reductions of the anterior sepal glands were registered in Tetrapterys and Janusia. This work reveals two distinct processes for gland loss in non-related groups of the family that resulted in similar present appearances. Our evaluation of the number of calyx glands and the processes of glandular loss in species with less than ten glands improves our understanding of the evolution of calyx glands in Malpighiaceae. © 2013 Elsevier GmbH.
Keywords: Calyx gland; Connation; Janusia mediterranea; Mascagnia cordifolia; Reduction; Tetrapterys chamaecerasifolia; evolutionary biology; morphology; phylogeny; taxonomy; ultrastructure; vine; Janusia; Malpighiaceae; Mascagnia; Tetrapterys